Improving School Leadership Through Support, Evaluation, and Incentives The Pittsburgh Principal Incentive Program - Hamilton, Laura S. (RAND Corporation, 2012)
This report examines Pittsburgh Public Schools' implementation and outcomes of the Pittsburgh Principal Incentive Program from school years 2007-2008 through 2010-2011, how principals and other school staff have responded to the reforms, and what outcomes accompanied program implementation.